دفع الإيهام وإزالة المشكل القرآني بالبلاغة والإعراب عند الإمام الفراء (Push the Inspiration, Remove the Quranic Problem in Rhetoric and Express at the Imam Al-Farra) - محمد عبد الجليل, محمد فتحي; محمد عبد الجليل, محمود فتحي (Journal of Islam in Asia (E-ISSN 2289-8077), 2021)
اهتم أهل التفسير بإزالة أي إشكال قد يتوهمه البعض، ولكن تكمن المشكلة في عدم شهرة الأساليب البلاغية والإعراب ضمن مسالك توجيه المشكل القرآني، وعليه فالبحث يهدف إلى إظهار كيفية دفع الإيهام عن الألفاظ القرآنية بالإعراب وتوضيح مكانة الأساليب البلاغية في ذلك عند الإمام الفراء، وقام البحث على المنهج التحليلي لتتبع تلكم الألفاظ والآيات التي يظهر فيها الإشكال عند من ليس لديهم الخبرة الكافية حول القرآن، وقد نتج عن هذا البحث أن الإشكال يمكن إزالته بالأساليب البلاغية وذلك ببيان مرجع الضمير، وبالتقديم والتأخير، وبدلالة الحذف، كما أن الإشكال قد يُزال بالإعراب والاستثناء وغيره. الكلمات المفتاحية: إشكال، البلاغة، الإعراب، الفراء، توجيه. Abstract The people of interpretation were interested in removing any forms that some might fancy, but the problem was that rhetorical methods were not well known and expressed within the direction of the Quranic problem. Therefore, the aim of the research is to show how to advance the inspiration for Quranic terms by expressing and clarifying the place of rhetorical methods in that way at the front of furs. The research was based on the analytical approach of following the words and verses in which the forms appear when those who do not have sufficient experience about the Quran have found that the forms can be removed in rhetorical terms by stating the reference of conscience, by submitting and delaying, by referring to deletion, and by expressing as an exception and otherwise. Keywords: Shapes, Rhetoric, Expression, Al-farra, Guidance.